Implementation of Smart Board Visual Media For Autistic Children in Grade 2 Indonesian Language Learning - Hariani Pertiwi; Aswasulasikin Aswasulasikin; Abdul Aziz; Muhammad Husni (IJE : Interdisciplinary Journal of Education, 2023)
This study aims to determine how the implementation of visual media "Smart Board" for Autism Spectrum Disorder (ASD) children in grade 2 Indonesian language learning. This research method uses qualitative, with this research design using descriptive qualitative. Qualitative research as a complex picture, detailed reports of respondents' views. This research was tested on grade 2 autistic students who experienced behavioural, communication and interaction barriers. The methods used in this research are observation, interviews, and documentation. The results of interviews with teachers and principals that the visual media "Smart Board" is able to accommodate autistic students in learning Indonesian, the material is in accordance with the level of ability of autistic children so that it is easy to understand and the design of the media display that can attract students' attention to use. So it can be concluded that the visual media "Smart Board" is very effective in supporting Indonesian language learning in the classroom as a tool for students to understand the material presented by the teacher.